Dissociation of Memory Systems: The Story Unfolds. - White, Norman M.; Packard, Mark G.; McDonald, Robert J. (Behavioral Neuroscience, 2013)
In this article we describe the ideas and circumstances that led to the experiment demonstrating a triple dissociation of memory systems. We then move on to discuss the results of 20 years of investigation of those ideas. First, evidence is described from animal studies consistent with the ideas that memory for different kinds of information is stored in different brain systems, and that the hippocampus, amygdala, and dorsal striatum are each central structures in one of the systems. We then focus on the 3 tasks used in the original triple dissociation: win-stay learning, conditioned cue preference, and win-shift learning. Each of these tasks is specific to behavior resulting from the type of information stored in one of the systems, but the use of other behavioral tests that are sensitive to the types of information stored in other systems has revealed that, in each case, other types of information are acquired in parallel. Next, evidence consistent with the idea that the outputs of the systems compete for control of behavior is discussed together with alternative forms of more direct interactions among the systems. Finally, some evidence that many of these ideas about multiple parallel memory systems may apply to humans is reviewed.